Probabilistic Sophistication and Reverse Bayesianism - Edi Karni; Marie-Louise Vierø (Queen's University, Department of Economics, 2013)
This paper extends our earlier work on reverse Bayesianism by relaxing the assumption that decision makers abide by expected utility theory, assuming instead weaker axioms that merely imply that they are probabilistically sophisticated. We show that our main results, namely, (modified) representation theorems and corresponding rules for updating beliefs over expanding state spaces and null events that constitute 'reverse Bayesianism,' remain valid.
Keywords: D8; D81; D83; 330; Awareness; unawareness; reverse Bayesianism; probabilistic sophistication